Pengukuran Kinerja Karyawan dengan Human Resources Scorecard di Pondok Pesantren Assyafiiyah Tamberu Batumarmar Pamekasan - Faiqoh Bahjah Lailatus Siyami; Terisa Sapta Dasyanti (Trunojoyo University of Madura, 2018)
Pondok Pesantren (Islamic Boarding School) is one of the oldest pedagogical institutions in Indonesia. Pondok Pesantren Assyafiiyah is one of Islamic BoardingSchools located in the area of Madura. To be a productive Islamic Boarding School (i.e.a boarding school which fits the need of pesantren), Assyafiiyah Islamic Boarding School needs to measure the performance of the employee. In this case, it is known as Board Performance which involves human resources, strategy, and performance. To produce a superior educational institution, the implementation of Human Resource Scorecard method that has a positive and significant effect on the institution of Assyafiiyah Islamic Boarding School is very necessary. It is used as an analysis of human resource performance. It is expected that this kind performance measurement system (i.e. Human Resource Scorecard) is able to provide the best solution in improving employee performance. Try Out is given and conducted on the institution to measure the performance system achievemet of its human resources. Therefore, the Key Performance Indicators which does not reach the target can be discovered. In other words, such kind of Try Out can be used to analyze the necessary refinement and improvement of the Key Performance Indicators previously mentioned. Based on the status quo, there are two major problems in this research: 1) how is the mapping of Human Resourse Scorecard?; and 2) what are the factors influencing the optimalization of Board Performance in Assyafiiyah Islamic Boarding School through Human Resource Scorecard?